Social Literacy: Nurses' Contribution Toward the Co-Production of Self-Management. (February 2021) - Dubbin, Leslie; Burke, Nancy; Fleming, Mark; Thompson-Lastad, Ariana; Napoles, Tessa M.; Yen, Irene; Shim, Janet K.
We share findings from a larger ethnographic study of two urban complex care management programs in the Western United States. The data presented stem from in-depth interviews conducted with 17 complex care management RNs and participant observations of home visits. We advance the concept of social literacy as a nursing attribute that comprises an RN's recognition and responses to the varied types of hinderances to self-management with which patients must contend in their lived environment. It is through social literacy that complex care management RNs reconceptualize and understand health literacy to be a product born out of the social circumstances in which patients live and the stratified nature of the health care systems that provide them care. Social literacy provides a broader framework for health literacy—one that is situated within the patient's social context through which complex care management RNs must navigate for self-management goals to be achieved.